When in Peril, Retrench : Testing the Portfolio Channel of Contagion. (IMF Working Papers; Working Paper ;, 2004)
One plausible mechanism through which financial market shocks may propagate across countries is through the effect of past gains and losses on investors' risk aversion. We first present a simple model on how heterogeneous changes in investors' risk aversion affect portfolio decisions and stock prices. Second, we empirically show that, when funds' returns are below average, they adjust their holdings toward the average (or benchmark) portfolio. In other words, they tend to sell the assets of countries in which they were "overweight," increasing their exposure to countries in which they were "underweight." Based on this insight, we construct a matrix of financial interdependence reflecting the extent to which countries share overexposed funds. This index can improve predictions about which countries are likely to be affected by contagion from crisis centers.